2010
DOI: 10.1002/bit.22710
|View full text |Cite
|
Sign up to set email alerts
|

Motif‐based search for a novel fructosyl peptide oxidase from genome databases

Abstract: The measurement of glycated hemoglobin A1c (HbA1c) has important implications for diagnosis of diabetes and assessment of treatment effectiveness. We proposed specific sequence motifs to identify enzymes that oxidize glycated compounds from genome database searches. The gene encoding a putative fructosyl amino acid oxidase was found in the Phaeosphaeria nodorum SN15 genome and successfully expressed in Escherichia coli. The recombinant protein (XP_001798711) was confirmed to be a novel fructosyl peptide oxidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 46 publications
3
8
0
Order By: Relevance
“…The flavin ring is shown for reference moiety of the ligand, although the sugar moiety presents a higher degree of mobility within the binding site of FPOX-E. Conversely, f-val shows a primary cluster that is more populated (67 % and 73 % of the time in FPOX-E and PnFPOX, respectively), which suggests that, overall, these enzymes have a higher affinity for f-val. This observation correlates well with the experimentally determined enzymatic activity of PnFPOX [24], while the enzymatic characterization of FPOX-E is incomplete [25]. Finally, we observe that both f-lys and f-val are highly unstable in the N1-1-FAOD enzyme, as suggested by the low population of the major conformational cluster (46 % for f-lys and 18 % for f-val) and by the high mobility of the substrates in the binding pocket, also involving the otherwise usually stable sugar moiety.…”
Section: Enzyme Structures and Sequence Comparisonssupporting
confidence: 89%
“…The flavin ring is shown for reference moiety of the ligand, although the sugar moiety presents a higher degree of mobility within the binding site of FPOX-E. Conversely, f-val shows a primary cluster that is more populated (67 % and 73 % of the time in FPOX-E and PnFPOX, respectively), which suggests that, overall, these enzymes have a higher affinity for f-val. This observation correlates well with the experimentally determined enzymatic activity of PnFPOX [24], while the enzymatic characterization of FPOX-E is incomplete [25]. Finally, we observe that both f-lys and f-val are highly unstable in the N1-1-FAOD enzyme, as suggested by the low population of the major conformational cluster (46 % for f-lys and 18 % for f-val) and by the high mobility of the substrates in the binding pocket, also involving the otherwise usually stable sugar moiety.…”
Section: Enzyme Structures and Sequence Comparisonssupporting
confidence: 89%
“…Kim et al . reported that G60 of PnFPOX is the decisive residue for F-VH oxidation activity 19 . Seventy-first residue and 59 residue (corresponding to G60 of PnFPOX) of AnFPOX-15 were structurally distant, as 71 residue is located in helix 2 and behind loop A, whereas 59 residue is located in loop A.…”
Section: Resultsmentioning
confidence: 99%
“…Fructosylvalylhistidine (Fru-ValHis) is released from HbA1c while fructosyl-lysine (Fru-Lys) is released from glycated albumin. Fru-ValHis and Fru-Lys can be considered as model compounds for HbA1c and glycated albumin, respectively (Kim et al 2010). However, wild-type FPOX has activities toward both Fru-ValHis and Fru-Lys.…”
Section: Introductionmentioning
confidence: 99%